2006
DOI: 10.1111/j.1537-2995.2006.00829.x
|View full text |Cite
|
Sign up to set email alerts
|

A flow cytometric method for detection and enumeration of low‐level, residual red blood cells in platelets and mononuclear cell products

Abstract: This method for determining rRBCs in blood products is accurate and repeatable with a lower limit of detection adequate to assess currently available blood products. FC should be considered for determining rRBCs in MNC products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 9 publications
6
13
0
Order By: Relevance
“…While the RBC content of each PC that was transfused during the study period was not quantified, quality control data from the participating centres indicated that the mean RBC content in PCs prepared from whole blood collections or obtained from apheresis devices was only 0·036 and 0·00043 ml, respectively (http://www.bancsang.net/en/professionals/resum_qualitat.html, last accessed 2 June 2014). These data, regarding the RBC content in PCs, are consistent with previous reports (Santana & Dumont, ; Culibrk et al , ). There is evidence that the minimum RBC volume necessary to elicit a primary anti‐D immune response is only 0·03 ml (Lozano & Cid, ), which is within the range of the quality control data from the centres in this study that transfused PCs prepared from whole blood collections.…”
Section: Discussionsupporting
confidence: 93%
“…While the RBC content of each PC that was transfused during the study period was not quantified, quality control data from the participating centres indicated that the mean RBC content in PCs prepared from whole blood collections or obtained from apheresis devices was only 0·036 and 0·00043 ml, respectively (http://www.bancsang.net/en/professionals/resum_qualitat.html, last accessed 2 June 2014). These data, regarding the RBC content in PCs, are consistent with previous reports (Santana & Dumont, ; Culibrk et al , ). There is evidence that the minimum RBC volume necessary to elicit a primary anti‐D immune response is only 0·03 ml (Lozano & Cid, ), which is within the range of the quality control data from the centres in this study that transfused PCs prepared from whole blood collections.…”
Section: Discussionsupporting
confidence: 93%
“…The level of residual red blood cells (rRBCs) in non‐RBC components for transfusion is of clinical interest due to potential morbidity related to ABO blood group mismatching and allo‐immunization to the Rh blood group antigen on RBCs [1]. In particular, high demand for platelet products and their short shelf life means that matching between platelet components and the recipient is not always possible.…”
Section: Introductionmentioning
confidence: 99%
“…Since the earliest studies described above [6][7][8][9] the RBC contamination of apheresis PLTs, collected using modern equipment, has fallen from 3 mL per product 6 to less than 0.0027 mL per product. 12,14,[16][17][18] This is far below the 0.03-mL threshold generally believed to be the minimal RBC inoculum required for alloimmunization of healthy volunteers, 19 and suggests that modern apheresis products do not convey a risk of D alloimmunization. 15 In October 2012, in concert with this evolving literature, our medical center's transfusion committee authorized a change in policy whereby the offer of RhIG (300 μg) to adult recipients of D-incompatible apheresis PLT transfusions would be restricted to D− women of childbearing potential (age ≤50 years) who receive a transfusion of D+ PLTs.…”
mentioning
confidence: 99%